Prevalence and Risk Factors of Human Herpes Virus Type 8 (HHV-8), Human Immunodeficiency Virus-1 (HIV-1), and Syphilis among Female Sex Workers in Malindi, Kenya. (20th June 2019) - Nzivo, M. M.; Lwembe, R. M.; Odari, E. O.; Kang'ethe, J. M.; Budambula, N. L. M.
Abstract : The prevalence of Human Herpes Virus type 8 (HHV-8), Human Immunodeficiency virus (HIV), and syphilis is high in Sub-Saharan Africa. Studies on HHV-8 in Kenya are few and data on its coinfection with HIV and syphilis scanty. This cross-sectional study among female sex workers (FSWs) in Malindi, Kenya, aimed to determine the prevalence of HHV-8, HIV, and syphilis mono/coinfections and identify associated risk factors. A total of 268 FSWs consented and were administered a structured questionnaire and screened for antibodies against HHV-8, HIV, and syphilis following the National Guidelines. FSWs positive for HHV-8 were 67/268 (25%), HIV 44/268 (16.4%), and 6/268 (2.24%) for syphilis. Eight out of 67 (12%) tested positive for HHV-8/HIV and 2/67 (3%) for HHV-8/syphilis coinfections. Married FSWs had higher odds of HHV-8 infection (OR 2.90, 95%, and P =0.043). Single marital status was inversely associated (OR 0.46, 95% CI 0.23-0.94, and P =0.034) with HIV infection. HIV was associated with increasing age (OR 14.79, P <0.001), inconsistent condom use (OR 2.69, P =0.004), increased duration as sex worker ≥6 (OR 3.0, P= 0.002) and clients ≥4 (OR 4.0, P< 0.001), intravenous drug use (OR 2.5, P =0.043), and early sex debut ( P= 0.049) unlike HHV-8 which was not associated with high risk sexual behavior. HHV-8/HIV coinfection was associated with increasing age (OR 11.21, P =0.027). Infection by HHV-8 was not significantly associated with HIV (OR 0.62; P =0.257) or syphilis (OR 1.52; P =0.636). There was a high likelihood of infection with HHV-8 compared to HIV (OR 8.6, P =0.014) and syphilis (OR 14.6, P <0.001). The lack of association of HHV-8 with high risk sexual behavior suggests that sexual transmission may not play a significant role in transmission of HHV-8 among FSWs in Malindi.